Antioxidant and Teratogenic Activities of Formulated Agar Extracted from Brown Seaweed Turbinaria conoides against Zebrafish Larvae. (11th July 2022) - Aavula, Thabitha; Narasimman, Vignesh; Ramachandran, Saravanan; Murugan, Radajurai; Ponnusamy, Murugavel; Pazhani, Gururaja Perumal; G, Sivaleela
Abstract : This study examines the antioxidant and teratogenic effects of two different type's methods of formulating agar from Turbinaria conoides ( T. conoides ) using a zebrafish model. The agar was extracted using the aqueous extraction method and developed in two different formulations using separate procedures. Formulated agar1 (FA1) used a higher concentration of the ingredients while formulated agar 2 (FA2) had a lesser concentration. The two unique formulated agars (FAs) were studied using biochemical composition, Fourier infrared (FT-IR) spectroscopy, gas chromatography-mass spectroscopy (GC-MS), and scanning electron microscopy (SEM). The antioxidant activities of both FAs in vitro were shown to be significantly different (P < 0.05 ) at various concentrations (60–180 μ l/ml) in the study. The toxicity of the FAs was dose-dependent, with FA1 having the least teratogenic activity when compared to FA2. In comparison to FA2, FA1 was found to have higher antioxidant activity. At various concentrations (0.5, 0.25, and 0.125 μ g/ml), the teratogenic activity of two FAs was examined in zebrafish embryos (ZFE) at 24, 48, 72, and 96 hours post fertilization (hpf). Both FAs exhibit dose-dependent toxicity and increased antioxidant activity, and this can be utilized as an alternative for standard antioxidants, according to this study.